2012
DOI: 10.1016/j.bbamem.2011.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane phospholipase A in phospholipid bilayers: A model system for concerted computational and experimental investigations of amino acid side chain partitioning into lipid bilayers

Abstract: Understanding the forces that stabilize membrane proteins in their native states is one of the contemporary challenges of biophysics. To date, estimates of side chain partitioning free energies from water to the lipid environment show disparate values between experimental and computational measures. Resolving the disparities is particularly important for understanding the energetic contributions of polar and charged side chains to membrane protein function because of the roles these residue types play in many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 59 publications
6
50
0
Order By: Relevance
“…The molecular dynamics calculations of OmpLA have been previously published (37). A similar protocol was used for PagP and OmpW in DLPC bilayers and is described in detail in SI Text.…”
Section: Measurement Of Folding Free Energies and M Valuesmentioning
confidence: 99%
“…The molecular dynamics calculations of OmpLA have been previously published (37). A similar protocol was used for PagP and OmpW in DLPC bilayers and is described in detail in SI Text.…”
Section: Measurement Of Folding Free Energies and M Valuesmentioning
confidence: 99%
“…Additionally, for cases in which the aqueous access to Arg may be impeded, structural manipulations to remove the obstruction can restore the accommodation of Arg within a bilayer (19). In relatively thin dilauroyl-phosphatidylcholine bilayer membranes, the cost of placing Arg within a transmembrane helix of outer membrane phospholipase is about 3.7 kcal/mol at pH 3.8 (13,16,18), whereas a somewhat larger cost was found for placing Lys at the same position at pH 3.8 (13). Within the context of the existing experiments and simulations, the pH dependence of side-chain ionization merits consideration.…”
mentioning
confidence: 99%
“…Although some molecular dynamics simulations (10,11) have estimated larger energy barriers than translocon-mediated (12) or water-to-bilayer membrane protein-folding experiments (13) for moving Arg into the bilayer, careful consideration of experimental conditions and the underlying molecular context is leading to a convergence of findings from different methods (14)(15)(16). In particular, Arg side-chain snorkeling, helix off-center translocation, and membrane deformation all can contribute to maintaining (partial) hydration and thereby lowering the free energy for accommodating a charged residue within a lipid bilayer (14)(15)(16)(17)(18). Additionally, for cases in which the aqueous access to Arg may be impeded, structural manipulations to remove the obstruction can restore the accommodation of Arg within a bilayer (19).…”
mentioning
confidence: 99%
“…Both DOPC and POPC have been previously applied to examine the interactions between lipid bilayers and amyloidogenic proteins (8, 16 -19). DLPC bilayers have been used in the study of a variety of membrane proteins and were observed to stabilize some membrane proteins in vitro that are less tractable with other lipid bilayer systems, but they have not been used previously in the study of A␤ (20,21).…”
mentioning
confidence: 99%